Weight Misperception among African American Adolescents: The Jackson Heart KIDS Pilot Study - Beech, Bettina M. (Ethn Dis, 2021)
BACKGROUND: Weight misperception is a common problem among adolescents; however, few studies have examined contributing factors among an exclusively African American population. The purpose of this study was to examine factors associated with weight misperception among 12- to 19-year-old participants in the Jackson Heart KIDS Pilot Study (JHS-KIDS). METHODS: Data were drawn from JHS-KIDS, a prospective, observational examination of cardiovascular-related risk factors among African American adolescents who were children or grandchildren of participants in the Jackson Heart Study. Adolescent weight misperception – discordance between measured weight status and perceived weight status – was the primary outcome of interest. Self-reported weight control behaviors, parent concerns about adolescents’ weight, parent-perceived responsibility for adolescent’s weight and daily hassles were the primary independent variables of interest. RESULTS: The analytic sample was equally divided by females (n=107) and males (n=105) and one third of study participants (33.5%) had discordance between their actual and perceived weight. Results from fully adjusted sex-stratified modified Poisson regression models indicated that weight behavior control was significant among females (PR = .66, 95%CI:1.20-2.30). Parental concerns about child weight were significant for males. Each additional point increase in the parent’s concern about their weight score was associated with a 9% increase in the adjusted prevalence of weight misperception among males (95%CI: 1.03-1.16). CONCLUSIONS: The sex-specific patterns in this study highlight heterogeneity among African American adolescents and an urgent need to consider sex and gender when developing targeted interventions for youth who are at high risk for weight misperceptions and unhealthy weight control practices.